Investigating the Impact of Plain Flap as Lift Enhancement on Symmetrical Airfoils - Parluhutan, Yohanes Mangatur; Fahrudin, Fahrudin; Rhakasywi, Damora (International Journal of Marine Engineering Innovation and Research, 2024)
Symmetric airfoils like NACA 0015 have limitations in generating lift compared to asymmetric airfoils. Therefore, additional devices are needed to overcome this limitation. This research analyzes the use of a lift enhancement device called a plain flap, which is installed on the trailing edge of the NACA 0015 airfoil using the CFD method. Simulations were conducted at a Reynolds number of  using the k-epsilon turbulent model. Three variations of geometry models were simulated: the NACA 0015 airfoil without a flap, the NACA 0015 airfoil with a plain flap at a deflection angle of 15°, and the NACA 0015 airfoil with a plain flap at a deflection angle of 30°. The simulation results show that the use of a flap can increase the maximum lift coefficient (Cl) of the airfoil. Initially, the maximum lift coefficient was 1.15 at an angle of attack (AoA) of 15°. With a plain flap deflection angle of 15°, the maximum lift coefficient increased to 1.5 at an AoA of 13°. With a plain flap deflection angle of 30°, the maximum lift coefficient further increased to 1.71 at an AoA of 10°. However, the use of a plain flap also leads to a significant increase in drag. On average, the drag coefficient (Cd) increased by 65% with a plain flap deflection angle of 15° and by 178% with a plain flap deflection angle of 30°.